2022
DOI: 10.1097/md.0000000000029438
|View full text |Cite
|
Sign up to set email alerts
|

Association between smoking and COVID-19 severity: A multicentre retrospective observational study

Abstract: The relationship between smoking and coronavirus disease 2019 (COVID-19) severity remains unclear. This study aimed to investigate the effect of smoking status (current smoking and a smoking history) on the clinical severity of COVID-19. Data of all enrolled 588 patients, who were referred to 25 hospitals in Jiangsu province between January 10, 2020 and March 14, 2020, were retrospectively reviewed. Univariate and multivariate regression, random forest algorithms, and additive interaction were used to estimate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…23 24 Previous studies showed that active smoking was related to increased risk of COVID-19 progression towards severe disease. 25 26 Furthermore, cancer survivors are considered to be under better hypertension control than the general population because they were more likely to engage in better hypertension management behavior. 27 Because higher uncontrolled blood pressure could contribute to a more severe disease course, 28 relatively well-controlled chronic diseases such as hypertension may have lowered the risk of hospitalization and hospitalization for severe disease after COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…23 24 Previous studies showed that active smoking was related to increased risk of COVID-19 progression towards severe disease. 25 26 Furthermore, cancer survivors are considered to be under better hypertension control than the general population because they were more likely to engage in better hypertension management behavior. 27 Because higher uncontrolled blood pressure could contribute to a more severe disease course, 28 relatively well-controlled chronic diseases such as hypertension may have lowered the risk of hospitalization and hospitalization for severe disease after COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…Many countries are affected by COVID-19. There are some studies reported in the literature on the association of COVID-19 and smoking [4] , [5] , [6] , [7] , [8] , [9] , [10] . Among them, Vardavas et al.…”
Section: Introductionmentioning
confidence: 99%
“…Polysaccharides are typically used as biological coating materials for preservation of okra. Adding physiologically active substances (e.g., phytic acid) to the polysaccharide coating solution can further improve the preservation effect (He et al, 2021). Recently, other techniques have been used to preserve fresh okra, including low-density polyethylene (Paulus et al, 2021) and nano-ZnO combined with ultraviolet irradiation (Ji and Wang, 2020).…”
Section: Introductionmentioning
confidence: 99%